WOMEN ATHLETES AT THE TOKYO 2020 OLYMPICS: VIEWS OF THE BRAZILIAN WRITTEN PRESS (Comunicação & Inovação, 2022)
The research sought to know the ideological content of the reports published in the special sections of three Brazilian newspapers about the participation of women athletes in the Tokyo 2020 Olympic Games, from a gender perspective. This is a documentary study with a qualitative approach. 157 reports were selected and submitted to thematic content analysis with the support of the software. The results reveal that the conquest of the Olympic medal is recent and difficult for women and the press was not critical and superficial about gender issues in this social space.
Keywords: Gender and health; Sports; Periodical